Analysis on the Acculturation of English to Sasak among Sasak Native Speakers - Khairunnasri, Muhammad (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
AbstractThe purpose of this research is to investigate the acculturation between Sasak language and English among Sasak native speakers, and to identify which words or phrases have been absorbed and used in Sasak daily communication. This research was conducted in Selakerat, Perian Village, Montong Gading District, Lombok Timur Regency. This research uses a qualitative descriptive method. The researcher employed observation, interview, and field note for data collection. The subjects of this study were nine native speakers of Sasak language of various ages residing in Selakerat. The results of this study indicate that language acculturation has occurred between Sasak language and English among Sasak native speakers in Selakerat, Perian Village in their daily communication. Some English words that have been absorbed and are frequently used in daily language include download, transfer, live, loading, log-in, by one, kill, like, top-up, reload, ID (identity), pet, peach, emote, skill, bot, gold, platinum, eyeliner, rank, map, lobby, account, make-up, cream, skincare, SIM (subscriber identity module), content, creator, skin, match, event, diamond, cream, viral, and pink, and several phrases like fake account (account fake), eye shadow, triple kill and trial emote (emote trial).